Inclusive education for inclusive economic participation: The financial access channel - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2020)
Purpose - The study assesses how inclusive education affects inclusive economic participation through the financial access channel. Design/methodology/approach - The focus is on 42 sub-Saharan African countries with data for the period 2004-2014. The empirical evidence is based on the Generalised Method of Moments. Findings - The following findings are established. First, inclusive secondary education moderates financial access to exert a positive net effect on female labour force participation. Second, inclusive "primary and secondary school education" and inclusive tertiary education modulate financial access for a negative net effect on female unemployment. Third, inclusive secondary education and inclusive tertiary education both moderate financial access for an overall positive net effect on female employment. In order to provide more gender macroeconomic management policy options, inclusive education thresholds for complementary policies are provided and discussed. Originality/value - Policy implications are discussed in the light of challenges of economic development in the sub-region and Sustainable Development Goals.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Gender; Inclusive development